Studi Evaluasi Kinerja Aparat Desa Dalam Meningkatkan Pelayanan Publik Ditinjau Dalam Perspektif Hukum Administrasi Negara : (Studi Kasus di Desa Pasar V Kebun Kelapa Kecamatan Beringin Kabupaten Deli Serdang) - Irma Tasya Harahap; Dani Sintara (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
Village officials are government employees in the field of public services who have duties and obligations towards services to the community who work and support the Village Head in carrying out his duties. In the relationship between the government and the community, various concepts are known such as state administrative law which studies the actions in organizing a country, including in villages. Public services are very necessary in fulfilling the desires and needs of the community in the village government.This research was conducted using a normative legal research method. The data collection methods used by the author were interviews and literature studies. Interviews are data collection techniques conducted through face-to-face and direct question and answer between researchers and informants, while literature studies are data processing conducted by systematically analyzing written legal materials with a statutory approach and a case study approach.The results of this study indicate that the performance of village officials in Pasar V Kebun Kelapa Village has not fully implemented good public service performance in terms of understanding of duties and functions, innovation, work speed, work accuracy and work between employees to realize excellent service.